Converted, Transgender, Angel: For an “Ethics of Visibility” in Contemporary Turkey: Преобратен, трансродов, ангел: За една „етика на видливост“ во современа Турција - Selvelli, Luis Miguel; Janeva, Kalina (Identities: Journal for Politics, Gender and Culture, 2007)
Author(s): Luis Miguel Selvelli | Луис Мигел Селвели Title (English): Converted, Transgender, Angel: For an “Ethics of Visibility” in Contemporary Turkey Title (Macedonian): Преобратен, трансродов, ангел: За една „етика на видливост“ во современа Турција Translated by (English to Macedonian): Kalina Janeva | Калина Јанева Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 2-3 (Summer 2007 - Winter 2008) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 37-54 Page Count: 17 Citation (English): Luis Miguel Selvelli, “Converted, Transgender, Angel: For an ‘Ethics of Visibility’ in Contemporary Turkey,” Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 2-3 (Summer 2007 - Winter 2008): 37-54. Citation (Macedonian): Луис Мигел Селвели, „Преобратен, трансродов, ангел: За една ‚етика на видливост‘ во современа Турција“, превод од англиски Калина Јанева, Идентитети: списание за политика, род и култура, т. 6, бр. 2-3 (лето 2007 - зима 2008): 37-54.